Gastric-type H+, K+-ATPase in mouse vestibular end organs. (4th May 2017) - Takumida, Masaya; Takumida, Hiroshi; Anniko, Matti
Abstract: Conclusion: Gastric type H +, K + -ATPase in the vestibular end organs may be of importance for K + circulation and may also be related to pH regulation in vestibular end organs and endolymphatic sac. Objective: To analyze the expression of gastric-type H +, K + -ATPase in normal mouse vestibular end organs. Methods: 8 weeks old CBA/J mice were used in this study. The presence of gastric-type H +, K + -ATPase α and β in the vestibular end organs, viz. utricle, saccule, ampulla, vestibular ganglion, and endolymphatic sac, was investigated using immunohistochemistry. Results: In the vestibular end organs, H +, K + -ATPase α and β were almost identical. H +, K + -ATPase was expressed in sensory cells, the basolateral surface of dark cells, fibrocytes, in vestibular ganglion cells, and in the upper region of the endolymphatic sac epithelial cells.